Estrategias proyectivas de espacio público sostenibles en el centro del municipio de Palmira - Valle del Cauca. (2023)
Sector 1 is located in the center of the municipality of Palmira, Valle del Cauca, where the greatest economic, commercial, cultural, historical and symbolic activity of the city resides.